2018
DOI: 10.3390/su10124741
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality Internship Programs—The Case of Romanian Business and Administration University Education

Abstract: To a large extent, research regarding internship programs emphasizes their crucial role in the future career of students. Business professionals and educators acknowledge the positive influence in the engagement of companies towards future potential employees. However, the quality of these internship programs in Romania is sometimes questionable and further research is needed in the field. Our paper aims at identifying and analyzing the main factors which influence the quality of an internship program from Rom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…In addition, several characteristics of internship experiences are related to career development, revealing their importance to the transition process from student to professional roles. Marinas et al. (2018) confirmed that there are five key factors influencing QNI for business and administration students' in Romania: job arrangements, mentorship and employability benefits, learning content, academic supervision, bureaucracy and accessibility.…”
Section: Literature Reviewmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, several characteristics of internship experiences are related to career development, revealing their importance to the transition process from student to professional roles. Marinas et al. (2018) confirmed that there are five key factors influencing QNI for business and administration students' in Romania: job arrangements, mentorship and employability benefits, learning content, academic supervision, bureaucracy and accessibility.…”
Section: Literature Reviewmentioning
confidence: 71%
“…An internship helps students who have clear idea about their career interest to apply what they learn in authentic, real-world contexts, and to acquire new experience and develop networks (Marinas et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that there exist 5 key factors influencing the quality of internship: job arrangements, mentorship and employability benefits, learning content, academic supervision, bureaucracy, and accessibility. The survey provides good insights for companies and universities about the quality dimensions of internship programs in the economic area (Marinas, et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beberapa penelitian terdahulu juga membahas peran penting dari program magang dalam niat karir masa depan mahasiswa perhotelan (Amanjeet Robinson et al, 2016;Wang, 2021). Karena di dalam program magang ini mahasiswa dipersiapkan untuk dapat memasuki pekerjaan di level awal dan melalui proses magang dapat melihat potensi nyata dari calon pekerja di masa depan (Marinaş et al, 2018). Program magang bagi mahasiswa di beberapa perguruan tinggi menjadi hal yang wajib untuk dijalankan dan merupakan bagian dari kurikulum (Brown et al, 2014;Moghaddam, 2014).…”
unclassified